Implementation of The Project Based Learning Model Lesson Study on Creativity, Abilitycreative Thinking, and Learning Outcomes - Nuraini, Nuraini; Afwan, Zainul; Sauri , Sofian; Ahmad , Zohiri; Wahyuningsih, Tuti; Aulia , Syarifah; Anwar, Muhammad (Sumber Belajar Sejahtera, 2024)
Application of the Project Based Learning (PjBL) Model Based on Lesson Study on Creativity, Creative Thinking Ability, and Learning Outcomes of Class II-B Students at SDN 1 Terara on Measuring Instrument Material. Based on the results of observations that have been made using students' learning practices in the field of Mathematics study in SDN 1 Terara for the 2023/2024 Even Semester Academic Year shows that students experience difficulties in mastering learning material on the subject of Measuring Instruments. Project Based Learning (PjBL) collaborated with Lesson Study (LS) is applied in this approach because LS is believed to be successful in improving learning practices. This implementation includes three aspects, namely: (a) Plan (Learning Planning), namely how a teacher designs learning so that students can learn actively. (b) Do (Learning Implementation) Implementation of learning that has been designed in the previous stage, where one teacher acts as a model and another teacher as an Observer of the learning. (c) See (Learning Reflection) After carrying out learning activities and observations, all parties involved reflect to discuss the learning that has been carried out and complete the parts that are still considered lacking.